2014
DOI: 10.5021/ad.2014.26.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Pruritus in Patients with Scalp Psoriasis and Their Relation with Intraepidermal Nerve Fiber Density

Abstract: BackgroundThe scalp is frequently affected in psoriasis patients, and pruritus can adversely affect the quality of life of affected patients. Few studies have assessed pruritus in scalp psoriasis.ObjectiveTo determine the correlation among the clinical characteristics of pruritus, psoriasis scalp severity index (PSSI), and intraepidermal nerve fiber (IENF) density in psoriatic scalp lesions.MethodsEighty patients (53 men, 27 women; mean age, 46.4 years; mean PSSI, 19.9) with scalp psoriasis were evaluated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
4
37
1
3
Order By: Relevance
“…Recently, it was also found that blocking Trk-A might be a valuable strategy for future antipruritic therapies. Recently, it was also suggested that increased epidermal nerve density in psoriatic scalp lesions may play a role in the development of pruritus in scalp psoriasis (Kim et al, 2014). In addition, increased innervation density in psoriasis induced by NGF may decrease the threshold for pruritic stimuli.…”
Section: Pathogenesis Of Pruritus In Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was also found that blocking Trk-A might be a valuable strategy for future antipruritic therapies. Recently, it was also suggested that increased epidermal nerve density in psoriatic scalp lesions may play a role in the development of pruritus in scalp psoriasis (Kim et al, 2014). In addition, increased innervation density in psoriasis induced by NGF may decrease the threshold for pruritic stimuli.…”
Section: Pathogenesis Of Pruritus In Psoriasismentioning
confidence: 99%
“…In some patients generalized pruritus is observed involving the entire body surface (Yosipovitch et al, 2000;Szepietowski et al, 2002;Amatya et al, 2008;Kim et al, 2014). Several authors documented a significant correlation between pruritus intensity and psoriasis severity (Szepietowski et al, 2002;Sampogna et al, 2004;Chang et al, 2007;Kou et al, 2012;Kim et al, 2014); however, not all researchers were able to confirm such a correlation (Yosipovitch et al, 2000). The mean severity of pruritus assessed according to the visual analogue scale (VAS) ranged from 4.2 to 6.4 points (Yosipovitch et al, 2000;Reich et al, 2003;Amatya et al, 2008); thus, it can be assumed that most patients with psoriasis suffer from pruritus of moderate severity.…”
Section: Clinical Characteristics Of Pruritus In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, scalp itch has been reported in up to 80% of patients with psoriasis, and there is positive correlation between the severity of the lesions in scalp psoriasis and the severity of itch [19] . Possible mechanisms that explain pruritus in scalp psoriasis are hyperinnervation, neurogenic inflammation, neuropeptide misbalance, abnormal functioning of the peripheral opioid system, cytokine release, and vascular abnormalities [20,21] . Regarding quality of life, pruritus is considered by patients as the most important factor that impairs the ability to work, with a negative impact on concentration in 52.5% of patients [15,22] .…”
Section: Psoriasismentioning
confidence: 99%
“…Regarding quality of life, pruritus is considered by patients as the most important factor that impairs the ability to work, with a negative impact on concentration in 52.5% of patients [15,22] . The characteristics of pruritus in scalp psoriasis are variable: most of the patients refer intermittent pruritus, and the most important exacerbating factors are stress and temperature [21] .…”
Section: Psoriasismentioning
confidence: 99%